Frequency of Supracondylar Humerus Fracture in Pediatric Patients at A Tertiary Care Hospital (Journal of Pakistan Orthopaedic Association, 2023)
Objectives: To determine the epidemiology of types of supracondylar humerus fracture in children with regards to treatment given, mechanism of fall and time of fracture.Material and Methods: This descriptive, cross-sectional study was carried out between 1st April 2018 and 1st April 2020 at the Department of Orthopaedics, Pakistan Railway General Hospital, Rawalpindi, Pakistan. The research involved patients up to the age of 12 years presenting the Emergency and Out patient Department with supracondylar humerus fractures for management. Age, gender, afflicted side, season in which fracture occurred, place of fall, type of Gartland's classification and the treatment given were noted on a predesigned proforma. The collected data were then statistically analyzed using SPSS.Results: Out of the 60 patients, mean age was 5.2±3.8 years. Majority of patients had fracture of the left elbow (n=36, 60%). Regarding gender distribution, it mostly affected the males (n=33, 55%). Regarding the type of fracture, majority of patients had Gartland type-III fracture (n=25, 41.67%). Majority of patients had a fall in the park (n=31, 51%), followed by home (n=13, 22%). Mostly these fractures occurred in the summer season (n=27, 45%).Conclusion: Gartland type-III are the commonest supracondylar humeral fractures in children. Mostly these fractures occur in summer season due to a fall.